1985
DOI: 10.1111/j.1540-6261.1985.tb02362.x
|View full text |Cite
|
Sign up to set email alerts
|

Dividend Policy under Asymmetric Information

Abstract: We extend the standard finance model of the firm's dividend/investment/financing decisions by allowing the firm's managers to know more than outside investors about the true state of the firm's current earnings. The extension endogenizes the dividend (and financing) announcement effects amply documented in recent research. But once trading of shares is admitted to the model along with asymmetric information, the familiar Fisherian criterion for optimal investment becomes time inconsistent: the market's belief … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

65
916
20
30

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 2,313 publications
(1,107 citation statements)
references
References 36 publications
65
916
20
30
Order By: Relevance
“…Hence, conflicts of interest and no direct observation from principal towards agent will lead to ethics issue, which will give rise to an extra cost. They also suggested that this conflict can be minimized by giving manager ownership options in form of stock options, perquisites and incentives so far well presented in the literature of corporate finance by Jensen and Meckling (1976), Watts and Zinmmerman (1978) and Miller and Rock (1985).…”
Section: "The Directors Of Such Companies However Being the Managermentioning
confidence: 99%
“…Hence, conflicts of interest and no direct observation from principal towards agent will lead to ethics issue, which will give rise to an extra cost. They also suggested that this conflict can be minimized by giving manager ownership options in form of stock options, perquisites and incentives so far well presented in the literature of corporate finance by Jensen and Meckling (1976), Watts and Zinmmerman (1978) and Miller and Rock (1985).…”
Section: "The Directors Of Such Companies However Being the Managermentioning
confidence: 99%
“…Numerous studies have examined whether payout increases or decreases convey favorable (unfavorable) information about future cash flow as found by signaling models (Bhattacharya, 1979;Miller & Rock, 1985). In sum, the results suggest that firms that increase their payout either through dividends or share repurchase experience an increase in their future operating performance and viceversa.…”
Section: The Choice Between Dividends and Share Repurchasesmentioning
confidence: 89%
“…Either dividends or share repurchases can be used to signal the undervaluation of a firm or to avoid agency costs (Gurgul & Majdosz, 2005). According to Miller and Rock (1985), dividends and repurchases are perfect substitutes and either announcement elicited the same market reaction. The results were consistent with the undervaluation and the free cash flow hypotheses.…”
Section: Interrelationship Between Dividends and Share Repurchasesmentioning
confidence: 99%
“…Some authors argue that dividends can convey information about future cash flows (Miller and Modigliani, 1961) and that managers may use dividend changes as costly signals of future earnings changes (Miller and Rock, 1985;Bhattacharya, 1979;John and Williams, 1985).…”
Section: Stock Returns Price Informativeness and Dividend Changesmentioning
confidence: 99%